(untitled) (Foro de Educacion, 2012)
African cinemas arose in the 1960s in concert with the movements of national independence and liberation. Due to the continent’s particular circumstances, the filmmaker came to serve the function of educating his compatriots, appropriating thereby the figure of the griot and moving toward the concept of the «griauteur». Making use of the cinematic medium and esthetic practices grounded in ethical praxis, directors such as Abderrahmane Sissako, Jean-Marie Teno, Haile Gerima and Mahamet-Saleh Haroun call cultural, social, and political realities into question, provoke reflection on the part of the spectator, and illuminate possible avenues of liberation for men and for women. Constrained by the exigencies of their specific historical circumstances, these directors have risen to become privileged negotiators both within their own societies and in the panorama of global cinema, taking their cue from such pioneers as Sembene Ousmane, Souleymane Cissé, and Djibril Diop Mambety.